Advances in fear memory erasure and its neural mechanisms - Wenbo Guo; Xibo Wang; Xibo Wang; Zihan Zhou; Zihan Zhou; Yuhui Li; Yuhui Li; Yani Hou; Keyan Wang; Ruyuan Wei; Xiaoyu Ma; Hao Zhang (Frontiers in Neurology)
BackgroundIn nature, animals must learn to recognize danger signals and respond immediately to threats to improve their environmental adaptation. However, excessive fear responses can lead to diseases such as post-traumatic stress disorder, wherein traumatic events result in persistent traumatic memories. Therefore, erasing pathological fear memories in vivo is a crucial topic in neuroscience for understanding the nature of memories and treating clinically relevant diseases.Main textThis article reviews recent studies on fear memory erasure, erasure of short- and long-term memory, fear memory erasure and neuroplasticity, the neural circuitry and molecular mechanisms of fear memory erasure, and the roles of engram cells and perineuronal nets in memory erasure.ConclusionResearch on the mechanism of memory erasure is limited, and a plausible explanation for the essential difference between memory erasure and memory extinction still needs to be provided. Notably, this review may guide future studies on fear memory and its underlying molecular mechanisms, which may help to develop novel treatment strategies for post-traumatic stress disorder, anxiety, and other mental disorders.